RELASI MANUSIA DAN ALAM DALAM NOVEL “CATATAN AYAH TENTANG CINTANYA KEPADA IBU” KARYA SANDI FIRLY: HUMAN AND NATURE RELATIONS IN THE NOVEL "FATHER'S NOTE ABOUT HIS LOVE TO MOTHER" FIRLY CODE WORKS - Silfia Mulyati; Dewi Alfianti; Lita Luthfiyanti (LOCANA, 2023)
Riset ini menitikberatkan pada sikap orang dalam mengenakan prinsip etika hidup serta tatanan hubungan orang dengan alam, mengisahkan peradaban marga Dayak Maratus, adat-istiadat, kepercayaan mengenai hutan sakti, serta keelokan alam Loksado. riset ini bermaksud buat menjelaskan hubungan orang serta alam dalam peringatan bapak mengenai Cintanya pada ibu ciptaan Sandi Firly. riset ini mengenakan prosedur deskriptif-kualitatif. Sumber data yang dibubuhkan adalah peringatan bapak mengenai Cintanya pada mama ciptaan isyarat Firly. riset ini mengenakan cara penelitian pustaka. analisis yang dilakukan adalah menjelaskan hubungan orang serta alam. Hasil riset membuktikan jika hubungan orang serta alam dalam melingkupi studi tindakan respek pada alam, studi tindakan tanggung jawab budi pekerti pada alam, studi tindakan simpati pada alam, studi tindakan kasih minat serta interes pada alam, serta studi tindakan tidak mengusik kehidupan alam. This research focuses on the attitude of people in applying the ethical principles of life and the order of people's relationships with nature, tells about the civilization of the Dayak Maratus clan, customs, beliefs about the sacred forest, and the natural beauty of Loksado. This research intends to explain the relationship between people and nature in a father's reminder about his love for Sandi Firly's mother. This research uses a descriptive-qualitative procedure. The source of the data attached is the father's warning about his love for his mother, created by Firly's sign. This research uses literature research methods. The analysis carried out is to explain the relationship between people and nature. The results of the research prove that the relationship between people and nature covers the study of acts of respect for nature, studies of acts of ethical responsibility towards nature, studies of acts of sympathy for nature, studies of acts of love, interest and interest in nature, and studies of actions that do not disturb natural life.